1968
DOI: 10.2135/cropsci1968.0011183x000800030026x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Quantitative Characters in Maize Inbred Lines, II. Effects on Performance in Single‐Cross and Double‐Cross Hybrids1

Abstract: Six inbred lines and seven single crosses involving these lines were obtained from four Corn Belt foundation seed stock organizations and the Iowa Agriculture Experiment Station. The genetic variation among the strains within inbred lines and among single crosses of the same pedigree was investigated. The inbred strains were compared in testcrosses with three unrelated inbred lines and the single crosses were compared in nine double‐cross hybrids. Tests in 10 environments, five locations for two years, reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Even since the 1950s, studies in maize have indicated significant phenotypic variation within inbred lines (Schuler, 1954; Hooker, 1955; Sprague et al, 1960; Russell et al, 1963; Busch and Russell, 1964; Fleming et al, 1964; Fleming, 1971; El‐Eryani and Fleming, 1966, 1968; Higgs and Russell, 1968a,b; Grogan and Francis, 1972; Russell and Vega, 1973; Bogenschutz and Russell, 1986; Tokatlidis, 2000). The variation was mainly searched by comparing sister lines obtained via selection within inbred lines, and was found to be transmissible to the hybrids.…”
Section: Intracultivar Heterogeneitymentioning
confidence: 99%
“…Even since the 1950s, studies in maize have indicated significant phenotypic variation within inbred lines (Schuler, 1954; Hooker, 1955; Sprague et al, 1960; Russell et al, 1963; Busch and Russell, 1964; Fleming et al, 1964; Fleming, 1971; El‐Eryani and Fleming, 1966, 1968; Higgs and Russell, 1968a,b; Grogan and Francis, 1972; Russell and Vega, 1973; Bogenschutz and Russell, 1986; Tokatlidis, 2000). The variation was mainly searched by comparing sister lines obtained via selection within inbred lines, and was found to be transmissible to the hybrids.…”
Section: Intracultivar Heterogeneitymentioning
confidence: 99%